2005
DOI: 10.1093/pcp/pci165
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Overexpression of Two Brassica CBF/DREB1-like Transcription Factors on Photosynthetic Capacity and Freezing Tolerance in Brassica napus

Abstract: The effects of overexpression of two Brassica CBF/DREB1-like transcription factors (BNCBF5 and 17) in Brassica napus cv. Westar were studied. In addition to developing constitutive freezing tolerance and constitutively accumulating COR gene mRNAs, BNCBF5- and 17-overexpressing plants also accumulate moderate transcript levels of genes involved in photosynthesis and chloroplast development as identified by microarray and Northern analyses. These include GLK1- and GLK2-like transcription factors involved in chlo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
118
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(123 citation statements)
references
References 77 publications
5
118
0
Order By: Relevance
“…The expression of GLK-1 in I. paraguariensis stressed leaves was induced 3-to 7-fold, depending on the severity of dehydration (Table 1). Savitch et al (2005) have reported that cold stress and cold acclimation of Brassica napus plants is associated with a moderate accumulation of mRNA for GLK-1 and GLK-2. Similarly, the amino acid composition is modified by environmental conditions and characterized by the elevated accumulation of specific amino acids involved in plant stress tolerance (Planchet and Limami, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The expression of GLK-1 in I. paraguariensis stressed leaves was induced 3-to 7-fold, depending on the severity of dehydration (Table 1). Savitch et al (2005) have reported that cold stress and cold acclimation of Brassica napus plants is associated with a moderate accumulation of mRNA for GLK-1 and GLK-2. Similarly, the amino acid composition is modified by environmental conditions and characterized by the elevated accumulation of specific amino acids involved in plant stress tolerance (Planchet and Limami, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, growers' major concern is good cold tolerance and yield. When biennial plants find themselves in low, non-freezing temperatures -they acclimate to cold undergoing genetic, morphological and physiological changes and therefore gaining freezing tolerance (Savitch et al, 2005). Low temperatures are very important for plant growth and survival, during autumn period plants acclimate and achieve better frost tolerance (Anurag et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…When plants are long-term cold acclimated, some morphological changes occur -they become dwarf, their leaves get thicker because of increased mesophyll cell size, specific leaf weight, decrease of leaf water content, etc. (Savitch et al, 2005). Therefore low temperatures have an important influence on the survival of plants and can change the peculiarities of plant growth and productivity -these changes occur due to the changes in gene expression (Kurbidaeva, Novokreshchenova, 2011;Lee, Tomashow, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…transgenic plants showed high root/shoot ratio that resulted in 20-30% more water uptake under dehydration condition. expression of several cBF-type genes in transgenic canola resulted in freezing tolerance and high photosynthetic activity (55). transgenic chrysanthemum with expression of AtDREB1A showed drought and salt tolerance and accumulated higher proline content and SoD activity (23).…”
Section: Dreb Expression Confers Abiotic Stress Tolerance In Transgenmentioning
confidence: 99%